The GRINDER CONSTRUCTION DESIGN OF A BALL MILL MACHINE FOR THE PROCESS OF HOMOGENIZING BLACK POWDER USING AN AUTOMATIC SYSTEM - Arif Setiawan; Dedy Pradigdo; Farid Hendro Wibowo (Jurnal Otoranpur, 2021)
Combat technology in the military world has undergone a very rapid development in both close combat and long-range combat. Long-range combat is identical to a rocket weapon where the rocket works because of the presence of an igniter that serves to burn the propellant so that when the propellant burns it will produce pressure that will push the rocket hurtling towards a predetermined target. Igniter is very important in the launch of rockets where the filling of the igniter is black powder that has been difficult to obtain because of the difficult manufacturing process and risk of explosion. This research aims to design a tool that can produce black powder with a large enough capacity and good quality and reduce the risk of explosions to support the manufacture of igniters for rocket launches, especially those owned by Indonesian Army. This research used pure experimental quantitative method with empirical calculations to obtain tools with the desired specifications. The results obtained after the calculation are the volume of octagonal prism tubes 2942.5 cm3, the total volume of steel balls with two size variations is 979.5 cm3, the maximum lendutan that occurs on the shaft of the player is 0.108 mm, so it is said to be safe.